FE stress analysis and prediction of the pull-out of FRP rods glued into glulam timber. Issue 2 (4th March 2022) - Khelifa, M.; Oudjene, M.; Ben Elechi, S.; Rahim, M.
ABSTRACT: This paper focuses on the FE analysis of the mechanical behavior of glued composite fiber-reinforced polymer (FRP) rods into glulam timber, using a 3D-continuum damage mechanics. The application of FRP to the glulam timber beams, despite the fact of limited investigations to date, offers an interesting and economic solution for strengthening in timber construction. In particular, the use of glued-in FRP rods for timber connections instead of steel is of great interest, due to the improved durability of the joint systems compared to their equivalent counterparts made of steel rods. For pull-out tests, the estimation of the mechanical response of glued FRP rods into glulam timber is very complex because of the combination of the three different materials: FRP rods, epoxy resin and glulam timber as well as the complexity of the expected brittle modes of failure of the timber. On the other hand, the existing prescriptive approaches (standard design codes) did not cover all the modes of failure expected within timber material and their predictivity is highly depending on the loading direction and on the rod material. There is, therefore, still a need to establish a general and predictive FE model to simulate accurately and cost-effectively the glued-in rod timber connections. In this study, a FE model combining 3D continuum damage mechanics (CDM) and cohesive zone modeling approaches is presented and its effectiveness was verified by comparison to experimental results available in the literature.